Hepatotoxicity following separate administration of two phosphodiesterase-5 inhibitors (sildenafil & tadalafil) and opioid (tramadol); evaluation of possible reversal following their withdrawal - Victor U. Nna, Ubom P. Akpan, Victoria E. Okon, Item J. Atangwho (Journal of Applied Pharmaceutical Science, 2015)
The use of phosphodiesterase-5 inhibitors (PDE5i) and tramadol in the absence of erectile and ejaculatory dysfunctions in Nigeria has become a norm. In this study, we comparatively assess the effects of chronic use of these drugs on hepatotoxicity. Fifty male albino wistar rats weighing 180–200g were randomly assigned into 5 groups (n=10) as follows; control, sildenafil (1mg/100g b.w), tadalafil (1mg/100g b.w), tramadol (2mg/100g b.w) and sildenafil+tramadol treated group (1mg/100g and 2mg/100g b.w, respectively). Drugs were orally administered, once, every two days for 8weeks, at the end of which five animals were sacrificed per group (batch 1), while the remaining five animals per group were allowed for another 8weeks without drug administration (batch 2). Serum concentration of liver enzymes (AST, ALT and ALP) and bilirubin were assessed in both batches. Serum concentrations of AST, ALT, ALP, total bilirubin and unconjugated bilirubin were significantly (p
Keywords: Hepatotoxicity, liver, phosphodiesterase-5 inhibitors, sildenafil, tadalafil, tramadol.